Actions of three clostridial IgA proteases on distinct forms of immunoglobulin A molecules - Hashim, Onn Haji; Hassan, H. (Wiley, 1991)
Three bacterial species of Clostridium (septicum, tertium and sporogenes) were identified to produce extracellular proteases cleaving IgA to Fab and Fc fragments, as demonstrated by SDS-PAGE and immunoelectrophoretic procedures. These enzymes acted on monometric IgA1 paraproteins and normal serum IgA1 but had no activity on IgA2 paraproteins and intact secretory IgA1 from human colostrum. Their action on polyclonal serum IgA1 suggested the absence of neutralizing anti-clostridial IgA protease activity. Although the enzymes were shown not to act on secretory IgA1, they were, however, able to digest free alpha-heavy chains of the dimeric IgA molecules. Susceptibility of the alpha-heavy chain to the proteases was more likely due to the change to a more accessible conformation than because of the absence of neutralizing anti-enzymic activity.